Analysis of business environment in hospitality companies in North Sumatera - Widia Astuty (Proceedings of AICS - Social Sciences, 2017)
The aim of the research is to find out the empirical evidence about the business environment which is faced by hospitality companies in North Sumatra. The business environment can be seen on an internal environment and an external environment. The internal environment consists of variables (advantage and disadvantage) which are inside of the company whereas the external environment consists of variables (threat and opportunity) which are outside the company. The research uses descriptive approach. The data collection is done by a survey which distributes a questionnaire to 113 the luxury hotel in North Sumatra. The result of the research shows that the business environment is viewed from the internal environment dimension with three indicators, namely organizational personnel, organizational function, and organizational level staff are in moderate-high uncertainty condition. Furthermore, the business environment is seen from the external environment dimension with five indicators, namely customers, suppliers, social, political, and technological competitors are in moderate-high uncertainty condition.